2021
DOI: 10.1002/lio2.671
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction in passive vs active smoking

Abstract: Background: The aim of this study is to assess the olfactory functions of passive smokers compared to active smokers and nonsmokers.Methods: This prospective case-control study included 30 nonsmokers, 30 passive smokers, and 30 active smoker participants. All groups were matched for gender and age. The Sino-Nasal Outcome Test 22 (SNOT-22) and Sniffin' Sticks test battery were administered to all subjects. Threshold (T), discrimination (D), and identification (I) scores were noted. Olfactory function was subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Concerning the effect of smoking on olfaction, literature suggests that smoking has a negative effect on olfactory sensitivity, making smokers less capable to recognize and discriminate flavors and also making them have a lower intensity perception 22 . Furthermore, the negative impact of smoking on olfactory functions is comparable for both active and passive smokers 33 . Chronicity and level of dependence on smoking is proposed to be associated with the rates of alterations in the sense of smell 23 .…”
Section: Discussionmentioning
confidence: 87%
“…Concerning the effect of smoking on olfaction, literature suggests that smoking has a negative effect on olfactory sensitivity, making smokers less capable to recognize and discriminate flavors and also making them have a lower intensity perception 22 . Furthermore, the negative impact of smoking on olfactory functions is comparable for both active and passive smokers 33 . Chronicity and level of dependence on smoking is proposed to be associated with the rates of alterations in the sense of smell 23 .…”
Section: Discussionmentioning
confidence: 87%
“…Factors contributing to age-related olfactory loss include degeneration of olfactory epithelium, conductive loss due to nasal obstruction, and central nervous system disorders 13 . Smoking is also a factor, with passive and active smoking negatively affecting olfaction, particularly olfactory threshold, recognition, and discrimination 14 . Gender is another factor, with women generally having better odor recognition abilities than men.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 11 studies showed a higher risk of OD in Neurologia i Neurochirurgia Polska 2023 www.journals.viamedica.pl/neurologia_neurochirurgia_polska current but not former smokers [37]. Çengel Kurnaz et al [38] demonstrated that olfactory functions were affected by both active and passive smoking. Smoking had the greatest impact on the odour detection threshold, followed by identification and discrimination [38].…”
Section: Discussionmentioning
confidence: 99%
“…Çengel Kurnaz et al [38] demonstrated that olfactory functions were affected by both active and passive smoking. Smoking had the greatest impact on the odour detection threshold, followed by identification and discrimination [38].…”
Section: Discussionmentioning
confidence: 99%